2002
DOI: 10.1051/0004-6361:20020896
|View full text |Cite
|
Sign up to set email alerts
|

Photocentric orbits from a direct combination of ground-based astrometry with Hipparcos

Abstract: Abstract. Complementing the Proper Motions of Fundamental Stars catalogue by Gontcharov et al. (CDS,) the photocentric orbits of some FK5/Hipparcos stars are calculated in a direct combination of the Hipparcos data with astrometric ground-based observational catalogues having epochs later than 1939. Some capabilities and limitations of this method are discussed in a comparison of our results with known orbits of Sirius, Procyon, Rasalhague, µ Cas and others. We conclude that this direct combination is an accep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…As mentioned before, Judge et al concluded that a main sequence companion would have to be a star later than G-type. A K-dwarf has a mass of between 0.6-0.8 M ; taking values of 1.1 -1.2M for δ And A gives 0.3-0.4 as the mass fraction, reasonably consistent with the value of Gontcharov & Kiyaeva (2002) of 0.5 ± 0.1. However, there are some discrepancies.…”
Section: Results and Conclusionsupporting
confidence: 60%
“…As mentioned before, Judge et al concluded that a main sequence companion would have to be a star later than G-type. A K-dwarf has a mass of between 0.6-0.8 M ; taking values of 1.1 -1.2M for δ And A gives 0.3-0.4 as the mass fraction, reasonably consistent with the value of Gontcharov & Kiyaeva (2002) of 0.5 ± 0.1. However, there are some discrepancies.…”
Section: Results and Conclusionsupporting
confidence: 60%
“…02225-2349 = κ For is a bright star with invisible component. Gontcharov & Kiyaeva (2002) proposed an astrometric orbit with a period 26.5 yr and semi-major axis α = 0. 26 ± 0.…”
Section: Discussion Of Individual Systemsmentioning
confidence: 99%
“…For many it should be possible to determine a photocentre orbit with semi-major axis a photo (Gontcharov & Kiyaeva 2002;Sahlmann et al 2015):…”
Section: Unresolved Binaries With Gaiamentioning
confidence: 99%